Agriculture and the WTO : creating a trading system for development - Ingco, Merlinda D.; Nash, John (Washington, DC : World Bank, 2004)
The book explores the key issues and options in agricultural trade liberalization from the perspective of these developing countries. Leading experts in trade and agriculture from both developed and developing countries provide key research findings and policy analyses on a range of issues that includes market access, domestic support, export composition, quota administration methods, food security, biotechnology, intellectual property rights, and agricultural trade under the Uruguay Round Agreement on Agriculture. Material is covered in summary and in comprehensive details with supporting data, a substantial bibliography, and listings of online resources. This book will be of interest to policymakers and analysts in the fields of development economics and commodities pricing and trade.
"A copublication with the World Bank and Oxford University Press."
Includes bibliographical references and index.
rpm 11/06/15
Loans
Keywords: International trade; Tariff on farm produce; Produce trade; Export subsidies; Free trade; Produce trade; Agriculture; Globalization; Developing countries